PENINGKATAN KREATIVITAS DAN HASIL BELAJAR PPKn MELALUI MODEL PROJECT BASED LEARNING DI KELAS VIII.2 SMPN 3 KOTO BARU - Anwar, Yenita (Ensiklopedia Education Review, 2020)
This research is a Classroom Action Research (CAR) with the aim of enhancing the creativity and learning outcomes of Class VIII.2 PPKn at SMPN 3 Koto Baru by using the Project Based Learning learning model. The study was conducted in two cycles, each cycle consisting of two meetings. As a data collection tool is an observation sheet and the results of student scores from tests given at the end of cycle I and the end of cycle II, the results obtained about the creativity of students at the initial observation only 38.5% of students who are creative, in cycle I increased by 64, 3% whereas in cycle II it increased again to 84.8%. For learning outcomes of 23.1% of students who achieved KKM in pre-cycle, increased 46,2% in cycle I and increased again to 76.9% in cycle II. This shows that the Project Based Learning learning model can be used as an alternative learning to increase student creativity and learning outcomes.